Réponses

Meilleure réponse !
2012-10-19T05:37:52+02:00

3*2^(x-2)+5*2^(x+1)=100

on utilise a^x=exp(xlna)

3exp((x-2)ln2)+5exp((x+1)ln2)=100

3exp(xln2-2ln2)+5exp(xln2+ln2)=100

on utilise exp(a-b)=exp(a)/exp(b) et exp(a+b)=exp(a)*exp(b)

3exp(xln2)/exp(2ln2)+5exp(xln2)*exp(ln2)=100

on utilise exp(2a)=(exp(a))² et exp(lna)=a

3exp(xln2)/(exp(ln2))²+5exp(xln2)*2=100

3exp(xln2)/2²+10exp(xln2)=100

(3/4)exp(xln2)+10exp(xln2)=100

((3/4)+10)exp(xln2)=100

(3/4+40/4)exp(xln2)=100

(43/4)exp(xln2)=100

exp(xln2)=400/43

on utilise ln(exp(a))=a

ln(exp(xln2))=ln(400/43)

xln2=ln(400/43)

x=ln(400/43)/ln2

 

2*3^(x+2)+22=15*3^(x+1)

on utilise a^x=exp(xlna)

2exp((x+2)ln3)+22=15exp((x+1)ln3

2exp(xln3+2ln3)+22=15exp(xln3+ln3)

on utilise exp(a+b)=exp(a)*exp(b)

2exp(xln3)exp(2ln3)+22=15exp(xln3)*exp(ln3)

on utilise exp(2a)=(exp(a))² et exp(lna)=a

2exp(xln3)(exp(ln3))²+22=15exp(xln3)*3

2exp(xln3)*3²+22=45exp(xln3)

18exp(xln3)+22=45exp(xln3)

45exp(xln3)-18exp(xln3)=22

27exp(xln3)=22

exp(ln3)=22/27

on utilise ln(exp(a))=a

ln(exp(xln3))=ln(22/27)

xln3=ln(22/27)

x=ln(22/27)/ln3